0.4x+3=-0.2x-0.6

Simple and best practice solution for 0.4x+3=-0.2x-0.6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.4x+3=-0.2x-0.6 equation:


Simplifying
0.4x + 3 = -0.2x + -0.6

Reorder the terms:
3 + 0.4x = -0.2x + -0.6

Reorder the terms:
3 + 0.4x = -0.6 + -0.2x

Solving
3 + 0.4x = -0.6 + -0.2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.2x' to each side of the equation.
3 + 0.4x + 0.2x = -0.6 + -0.2x + 0.2x

Combine like terms: 0.4x + 0.2x = 0.6x
3 + 0.6x = -0.6 + -0.2x + 0.2x

Combine like terms: -0.2x + 0.2x = 0.0
3 + 0.6x = -0.6 + 0.0
3 + 0.6x = -0.6

Add '-3' to each side of the equation.
3 + -3 + 0.6x = -0.6 + -3

Combine like terms: 3 + -3 = 0
0 + 0.6x = -0.6 + -3
0.6x = -0.6 + -3

Combine like terms: -0.6 + -3 = -3.6
0.6x = -3.6

Divide each side by '0.6'.
x = -6

Simplifying
x = -6

See similar equations:

| 5x+5=3x+4+2x+1 | | x^2+bx+6.25=0 | | 90=2x+10 | | X+y=122 | | -3(4+3)=2y+3 | | 17-3=4x | | -3(q-7)=2+q-21 | | 2x+1=2(x-4) | | 3x^5/6-16=80 | | 2x+1=2(x-8) | | x-5+4x+x+x-8=360 | | 3x-7(x+6)=14 | | 2/3x=1=-1/3x-1 | | 20(-9+6)=-6(x-2) | | 4(3-z)-36=26z-6(4+5z) | | y=c(x-2) | | 4sin^2x+11sinx-3=0 | | 4(3+x)=-4-x | | 1/2(2p-12)=10p | | 12+3x=1.2-4x | | 12+3x=1.24x | | 1n-4=3n+6 | | x+100=3x+50 | | 3(a-3)+6=12 | | y=1/-1/4 | | (.33333)d-5=81 | | -d+5=4 | | -12-5[6-(2*6)]=18 | | 16x^4-7x^2-18=0 | | (1/3)d-5=81 | | -1n+-2+6=-9+8n+4 | | 6y-5=-2x+11 |

Equations solver categories